Pengaruh Dimensi Fraud Diamond dan Penyalahgunaan Teknologi Informasi Terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi saat Perkuliahan Online - Yayuk Nurjanah; Eka Puji Anggraeni; Jonathan Van Melle (Forum Dosen Indonesia, 2021)
This study aims to determine the effect of the fraud diamond dimensions consisting of pressure, opportunity, rationalization, and ability, as well as the effect of misuse of information technology on the academic cheating behavior of accounting students during online lectures. The author chooses students of the accounting study program of West Java province as the research subjects. This type of research is a quantitative research. The sample selection technique used purposive sampling, in determining the sample size of 384 samples. The data analysis technique used was multiple linear regression analysis using SPSS version 16 software. The results showed that partially the pressure variable had no significant effect on the academic cheating behavior of accounting students, while opportunity, rationalization, ability and misuse of information technology had a significant effect on fraudulent behavior. academic accounting students. Simultaneously, all independent variables have a significant effect on the academic cheating behavior of accounting students. Keywords: Academic Fraud Behavior, Fraud Diamond (Pressure, Opportunity, Rationalization, and Ability) and Information Technology Misuse